Physicochemical characterization of Shadguna Balijarita Makaradhwaja: A preliminary study - Khedekar, Sanjay Bhausaheb (Ayu, 2016)
BACKGROUND: Makaradhwaja, a herbomineral preparation, is a popular aphrodisiac and rejuvenator in traditional medicine. It is prepared from purified gold, mercury, and sulphur in different proportions by the application of gradually increasing heat in modified electrical muffle furnace (Valuka Yantra). To find out major and minor trace elements and structural composition of Makaradhwaja, its chemical characterization is needed. AIM: This study aims to develop preliminary physicochemical profile of Shadguna Balijarita Makaradhwaja (SBM). MATERIALS AND METHODS: Physicochemical characterization of Shadguna Balijarita Makaradhwaja was carried out by adopting various techniques, viz. X-ray diffraction, inductively coupled plasma optical emission spectrometry (ICP-OES), and Fourier transform infrared spectroscopy to determine structure and contents. RESULTS AND CONCLUSION: Shadguna Balijarita Makaradhwaja contains 12131 ppm of gold in inductively coupled plasma optical emission spectrometry study. FTIR study revealed few organic compounds. Structurally, it is a mercuric sulfide having an empirical formula HgS.